Kesesuaian Fungsi Taman Kota dalam Mendukung Konsep Kota Layak Huni di Surakarta - Iswara, Resi; Astuti, Winny; Putri, Rufia Andisetyana (ARSITEKTURA, 2017)
Livable city is a city where people can have a healthy life and have the ease of movement.. Surakarta is one of the top ten livable cities in Indonesia in 2014. Surakarta became candidate of the most comfortable and livable city in Indonesia because it shows progress in terms of infrastructure improvements, utilities, public space, accessibility, transportation, and other criteria. One of the public spaces in Surakarta which is rapidly developed is the city parks. The number of city parks in Surakarta is multiplied in the last 10 years. But many parks are eventually abandoned and not maintained, misused and damaged. This research question is how the conformity functions of city parks in Surakarta in supporting the concept of a livable city? Is the city park suitable for the concept of  livable cities in Surakarta? The aim of this study is to determine the conformity of the function of a city park in Surakarta in supporting the concept of a livable city. The research is a quantitative using scoring analysis and descriptive analysis. Scoring analysis is used to find the conformity function of city parks in Surakarta. Then the research finding is described by using the descriptive analysis. The variable of this research consists of the social activity functions, educational functions and economic functions. Based on the analysis performed, the result of this study shows only one garden is conform  in supporting the concept of a livable city, while others only quite suitable  in supporting the concept of a livable city. Keywords: livable city, city parks, conformity, compliance function of  city parks.